ANALISIS PILAR INFRASTRUKTUR YANG MEMPENGARUHI DAYA SAING DAERAH KABUPATEN WONOGIRI - Lilyk Eka Suranny (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
Infrastructure is one of the pillars that influence regional competitiveness. The purpose of this study is to analyze the infrastructure pillars that influence the Regional Competitiveness Index (IDSD) of Wonogiri Regency and provide recommendations to increase the competitiveness of Wonogiri Regency in the infrastructure pillars. Data collected of secondary data based on the attributes of the questionnaire that has been set in the assessment of regional competitiveness. Data comes from central government and regional OPDs, universities, research institutions and other official institutions. Data analysis used quantitative and qualitative descriptive analysis to analyze the results of the IDSD assessment in Wonogiri Regency especially on infrastructure pillars. The results showed that the IDSD value of Wonogiri Regency in the infrastructure pillar was below the average value of the competitiveness index of the regency / city in Central Java. The infrastructure pillar is formed from the dimensions of transportation infrastructure and the dimensions of clean water and electricity infrastructure. The low value of regional competitiveness in infrastructure pillars is that road infrastructure with poorly / damaged conditions is still found in several regions / sub-districts in Wonogiri and the number of public transportation facilities is decreasing. From the dimensions of clean water infrastructure, the percentage ratio of the number of clean water customers compared to the total population is 80,31% and 19,69% of the people do not get clean water. From the electricity dimension, the percentage of electricity customers in Wonogiri Regency is 89,29%, but some houses scattered in several sub-districts are still not connected with electricity.